Kapasitas Pemerintahan Afghanistan Rezim Taliban Baru Sebagai Peserta Dalam Perjanjian Internasional - Miko Aditiya Suharto; Maria Novita Apriyani (Jurnal Risalah Hukum, 2022)
The decision by the United States and NATO to withdraw troops from Afghanistan is a golden opportunity for the ultraconservative political factions (Taliban) to take back their control of Afghanistan. This military invasion by the United States and NATO has caused a humanitarian tragedy and an extraordinary humanitarian crisis in Afghanistan since 2001 ago. The Taliban took control of the government in Afghanistan after the United States and NATO withdrew their troops from Chief Ashraf Ghani. This article is a legal scientific article that has been normatively researched, the approaches used in writing this article include the statutory approach and case studies (not a case approach). This article discusses the legitimacy of the occupation of the Afghan government by the Taliban regime, as well as the legal consequences that arise from international agreements that have been made and run from the previous government regime. Conclusion This Scientific Article states that the Status of the Government of Afghanistan by the Taliban is a Succession of Government and is legal under international law and the impact of this succession makes the current Regime Government a Successor of the previous government, so that the Rights & Obligations of the existing International Agreements remain binding on the State of Afghanistan even though it has been change government regime. Keywords: succession, taliban regime, afghanistan, international law